PENINGKATAN HASIL BELAJAR MENENTUKAN KELILING DAN LUAS JAJAR GENJANG DAN SEGITIGA MELALUI STRATEGI PEER LESSONS SISWA KELAS IV SDN CAMPURSARI KECAMATAN SAMBIT KABUPATEN PONOROGO - Istiningsih, Sri (Educatio Vitae, 2016)
The research which is aimed to know the improvement in comprehending the concept of determining the circumference and the area of paralellograms and triangles through the method of Peer Lessons towards the fourth graders of Sambit State Primary School in Ponorogo in semester I 2013-2014 academic year is a class act research which is conducted towards 19 students in 3 cycles consisting of 6 meetings. Each meeting consists of 2 X 35 minutes. Each cycle includes the activities of planning, implementation, observation, and reflection. The data are taken by using test instruments, interviewing, distributing questionnaires and journals. The Peer Lessons strategy is proven to have capability  in improving the comprehension of mathematics concept in the topic of “determining the circumference and the area of parallelograms and triangles” which is noticed by the improvement of mean score in which it is 72.37 in cycle I; 75.53 in cycle II; and 80.53 in cycle III. Moreover, there is also the percentage improvement of the learning accomplishment in which it is only 68.42% in cycle I, then, it is improving into 78.95% in cycle II and 94.74% in cycle III. The research proves that the use of Peer Lessons strategy is capable to improve the comprehension of mathematics concept in the topic of “determining the circumference and the area of parallelograms and triangles.” Key Words: Concept Comprehension, Peer Lessons, Mathematics